Teaching the methods of solving mathematical problems (Journal of Educational Sciences, 2023)
Following questions was affected in this article – types of mathematical problems, role and meaningof solving problems in men’s life (pupil, student), difficulties in solving mathematical problems,classification of mathematical problems due to the way of solving key. Tasks of arithmetics are variousaccording to the contents and on difficulty of the decision. At the solution of some tasks doesn’t meetdifficulties in a choice of this or that action. The choice of arithmetic actions and at the solution of manytasks is carried out on the basis of the communications existing between these sizes. Solution of eachtask purely arithmetic actions and logical conclusions, but not to the same extent: in one tasks arithmeticactions prevail, and reasonings and logical conclusions play so prevailing role others, after the logicalconclusions the solution of a task is consolidated to thought tension. If the necessary data on arithmeticsare acquired and problems of detailed type are already sorted, other problems of this sort are solvedwithout effort. The article presents the results of a survey of teachers on the methodology of teachingmathematics and solving problems by schoolchildren.Key words: quantily , problem, teaching the methods of problem solving , types of arithmeticalproblems , ways of problem solving.